Islamism, Government Regulation, and the Ahmadiyah Controversies in Indonesia - Ismatu Ropi (Al-Jami'ah Research Centre, 2010)
Over the past three decades, Ahmadiyah has been at the center of one of the most significant controversies within the Indonesian Muslim community, particularly after the issuance of MUI’s (Majelis Ulama Indonesia/The Council of Indonesian Ulama) Fatwas in 1980 and 2005 respectively. This paper undertakes a discussion of Ahmadiyah, reviewing its initial contacts with several Muslim organizations such as Muhammadiyah and Syarikat Islam, its roles in disseminating the idea of progressive and modern Islam among Muslim scholars in 1940s to 1960s. The second part will review internal and external factors contributing to the issuance of MUI Fatwa 1980 in the light of preserving orthodoxy within the Indonesian Muslim community. It will also highlight in brief the government response toward the Ahmadiyah’s case. The last part focuses mainly on the Fatwa 2005 and its impact on the more strained relationships within the Muslim community in Indonesia. It will examine socio-political conditions before and after the Fatwa 2005 in light of the steady rise of a new model of Islamism in Indonesia and the conservative shift within the MUI itself, particularly after the downfall of the New Order’s regime in 1998. The arguments ‘pro and contra’ Fatwa 2005, as well as the ‘awkward position’ of the new government on this issue, will be analysed in detail.